1999
DOI: 10.1097/00001756-199904060-00008
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of sexual dimorphism in human corpus callosum

Abstract: To study the sexual dimorphism of human corpus cauosum (CC), we analyzed the midsaggital magnetic resonance imaging (MRI) morphometry in 67 adults aged (mean+/-s.d.) 36.82+/-9.35 years. Four specific angles of the CC were determined. All four angles in 34 females and 33 age-matched males showed a significant difference between females and males. These morphometric findings confirm a gender difference in the orientation of corpus callosum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 8 publications
1
23
0
2
Order By: Relevance
“…There was a statistically significant difference in the midsaggital area between right handed and left handed [14] 661±9 663±7 Kertesz et al [16] 724* 716* Clarke et al [5] 540* 550* Pujol et al [19] 577±115 582±91 Hardan et al [15] 671±100** Mostofsky et al [25] 627±73** Oka et al [18] 657±80** Laissy et al [17] 636** Suganthy et al [7] 700±84* *Sd Not Presented **No Gender Specified subjects (p=0.048). Also, there was a statistically significant difference in r3 distance between those using their right hand and those using their left hand in cleaning the blackboard (p=0.041) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a statistically significant difference in the midsaggital area between right handed and left handed [14] 661±9 663±7 Kertesz et al [16] 724* 716* Clarke et al [5] 540* 550* Pujol et al [19] 577±115 582±91 Hardan et al [15] 671±100** Mostofsky et al [25] 627±73** Oka et al [18] 657±80** Laissy et al [17] 636** Suganthy et al [7] 700±84* *Sd Not Presented **No Gender Specified subjects (p=0.048). Also, there was a statistically significant difference in r3 distance between those using their right hand and those using their left hand in cleaning the blackboard (p=0.041) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Oka et al [17] have reported gender differences in four specific angles of the CC. We found the angle of genu as 74.06±19.98º in male, and 69.61±16.36º in female.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is not much reason to assume that the CC functions in a predominantly inhibitory fashion in males and a predominantly excitatory fashion in females. While some researchers have claimed that the female CC, if scaled relative to whole brain size, is larger and thus facilitates transfer of information between the hemispheres (Oka et al, 1999; Mitchell et al, 2003), others have not found a difference (Bishop and Wahlsten, 1997; Luders et al, 2006; Zarei et al, 2006). Thus, there is little reason to speculate on the possibility of males and females differing with regard to the relation of tinnitus to callosal structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…Oka ve ark. [19] ise A ve C açılarının erkeklerde, B ve D açılarının ise kadınlarda geniş olduğunu belirtmişlerdir. Her iki çalışma da normal bireylerde yapıldığından bizim çalışmamızda cinsiyet karşılaştırması her iki grupta ayrı olarak yapılmıştır.…”
Section: Discussionunclassified